Noteworthy records of Jaguar Panthera onca in Guatemala - García, Manolo; González-Castillo, Vivian; Gaitán, Carlos; Guzmán-Flores, Gerber; Sandoval-Lemus, Mynor; Leonardo, Raquel; Lobos, A. Lorena; Cajbon-Vivar, M. Gabriela; Aguilera, Andrea (Therya Notes, 2020)
The jaguar is the largest terrestrial carnivore in America. According to the International Union for the Conservation of Nature, its conserva- tion status is “Near Threatened” in its distribution range. In Guatemala, the jaguar is mainly distributed in the Maya Biosphere Reserve (MBR). In the years 2016 and 2018, camera-trapping studies were conducted in the San Miguel La Palotada-El Zotz Protected Biotopo (BPSMPZ) and in Yaxhá Nakum Naranjo National Park (PNYNN), respectively; both core zones of the MBR. Eight camera-trap stations were installed in BPSMPZ and 5 in PNYNN during the dry season, with at least 90 trap-days/nights in each site. In BPSMPZ, one adult jaguar of undetermined sex was recorded in one of the eight sampling stations installed; in PNYNN, there were 22 records (independent events) of at least 6 adult individuals (1 female, 3 males, 2 of undetermined sex) in three of the five sampling stations installed. This work reports important records on the presence of jaguars in core zones currently under pressure from human activities conducted within the southern limits of the MBR. Maintaining the integrity of these two areas is imperative to preserve this species in the MBR.